"a creature native and indued/ Unto that element"? Digitizing _Hamlet_: How to Start; Where to Stop - Willcox, P (Digital Research Infrastructure for the Arts and Humanities (DARIAH), 2011)
Confronted with the task of publishing online 32 XML-encoded texts of Hamlet in quarto in the space of one year, the Shakespeare Quartos Archive (SQA) moved away from a traditional, editor-led approach to focus instead on end-users. This paper explores the process of the selection of and engagement with this audience, and assesses the effectiveness of this approach in terms of the digital editions, encoded to Text Encoding Initiative (TEI) p5 standard, and of the web interface the project created.